Sagot :
Answer:
This is asking for the value of the function g(x) = -x2 + 3x - 2 when x = -4 [g(-4)].
Just use "-4" when x appears in the equation.
g(-4) = - (-4)2 + 3(-4) - 2
g(-4) = -16 - 12 -2
g(-4) = -30
I hope this helps
Step-by-step explanation:
For this problem, all you have to do is substitute the (-4) in for the variable x within the equation -x2+3x-2
In order to avoid simply giving away the answer, I will create a similar example.
Solve f(x) = -x2 - 5x + 4 when x = -3
First, replace every x with the (-3).
f(-3) = -(-3)2 - 5(-3) + 4
Next, follow your order of operations (PEMDAS). Since there are no operations in parentheses, we will go straight to exponents.
f(-3) = -(9) -5(-3) + 4
Make note of the fact that the negative in the original equation was NOT squared because it was not part of x. You would only square the outside negative as well if parentheses surrounded it like so (-x)2. Now, we need to multiply and divide, from left to right.
f(-3) = -9 + 15 + 4
Now we just add and subtract from left to right to find the final answer.
f(-3) = 10
I trust that using this example to guide your own problem will both help you get your own answer and understand the process yourself. Good luck!
Answer:
g(-2)= 3x+2
g(-2)= 3(-2)+2
g(-2)= -6+2
g(-2)= -4 / x-4
g(-2) = x
Step-by-step explanation:
yung -2 sunstitute molang sa ex then continue the solving after mo makuha ang sagot i divide mo sa denominator o -4/-4 is one di mona ilalagay kasi alangan naman 1x diba? so x nalang g(-2) is x